Polycystic Ovary Syndrome: An Update on Management Strategies - Mansoor Aftab, Muhammad Inzamam, Shahid Latif (Pakistan Journal of Medical & Health Sciences, 2022)
In the reproductive years of a female, she often comes up with a common disorder known as polycystic ovary syndrome also called as PCOS. In this disorder the level of androgen, male hormone, increases above the normal level that causes ovulatory dysfunctioning. Moreover, this disorder also causes severe metabolic anomalies, specifically weight gain and insulin resistance which is a well-known attribute of the pathophysiology of PCOS. PCOS leaves adverse impacts upon the ovarian cycle and fertility of women. This review paper encapsulates possible treatments present for PCOS in females by discussing current and potentially available options.